2020
DOI: 10.1088/1757-899x/918/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Development of road transport infrastructure through the construction of a runway in the city of Tobolsk

Abstract: This article discusses the construction of a runway in the city of Tobolsk. The development of road transport infrastructure will allow the territory to open up new opportunities. The author examines the structure of the construction of the runway, analyzes the necessary costs for the construction of a road transport facility. Highlights the main prospects for further development of the territory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Environmental protection and rational use of natural resources is currently the most discussed and relevant topic not only in our country, but also around the world [1]. After all, the well-being of future descendants depends on the life activity of today's generation, and accordingly, one of the important tasks is the preservation of natural resources [2].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental protection and rational use of natural resources is currently the most discussed and relevant topic not only in our country, but also around the world [1]. After all, the well-being of future descendants depends on the life activity of today's generation, and accordingly, one of the important tasks is the preservation of natural resources [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, environmental studies conducted in many countries of the world have shown that the increasing destructive impact of anthropogenic factors on the environment has brought it to the brink of crisis. Among the various components of the environmental crisis are the depletion of raw materials, the lack of clean fresh water, ferrous and non-ferrous metallurgy, possible climate disasters [1]. The problem of irreplaceable natural resources -air, water and soil by industrial and transport waste-has become the most threatening.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that pollution of the hydrosphere, atmosphere and lithosphere creates an extremely unfavorable environmental situation. Environmental issues in the XXI century are always relevant for the whole planet, for our country, and for its particle -the Kurgan region [1].…”
Section: Introductionmentioning
confidence: 99%